ANTIDIABETIC AND ANTIDYSLIPIDEMIC EFFECTS OF HELIOTROPIUM STRIGOSUM IN RAT MODELS OF TYPE I AND TYPE II DIABETES. - Chaudhry, Shafqat Rasul; Akram, Adnan; Aslam, Naveed; Asif, Muhammad; Wajid, Muhammad; Kinfe, Thomas Mehari; Jabeen, Qaiser; Muhammad, Sajjad (Acta Poloniae Pharmaceutica, 2016)
Heliotropiumz stnigosum Wilid. (Boraginaceae) is used traditionally as a laxative, diuretic, and as a treatment for snake bites and stings of nettles. Recent investigations have shown anti-inflammatory and antioxidant activity of H. sorigosum. However, antihyperglycemic and antidyslipidemic activity of H. strigosum has not been investigated to date and we aimed to explore these activities of the crude aqueous methanolic extract of thEaerial parts of H. strigosum (Hs.Cr). Hs.Cr was administered orally at doses of 100, 300, and 500 mg/kg in alloxan-induced diabetic rats (type I diabetes) and fructose-fed rats (type II diabetes). The fasting blood glucose (FBG) concentration was assessed by glucometer, while semum total cholesterol, triglycerides and HDL were estimated by using standard kits. The FBG concentration significantly (p < 0.05) decreased in dose-dependent pattern in both alloxan-induced diabetic and fructose-fed rats on Hs.Cr administration. The percentage glucose reductions in alloxanized rats with glibenclamide, Hs.Cr 100, 300, and 500 mg/kg were obeserved to be 67, 36, 56 and 62%, respectively. In fructose-fed rats, the percentage glucose redutions associated with metformin, Hs.Cr 100, 300, and 500 mg/kg were 23, 5, 11 and 12%, respectively. The extract also corrected the dyslipidemia associated with fructose and alloxan-induced diabetes by significantly (p < 0.00 1) decreasing the concentration of serum total cholesterol, triglycerides and LDL and by increasing HDL concentration. Our data demonstrate that the H. stigosum has antidiabetic and antidyslipidemic effects, thus encouraging further studies. <br